Figures 38-44 from: Crabo L, Davis M, Hammond P, Mustelin T, Shepard J (2013) Five new species and three new subspecies of Erebidae and Noctuidae (Insecta, Lepidoptera) from Northwestern North America, with notes on Chytolita Grote (Erebidae) and Hydraecia Guenée (Noctuidae). ZooKeys 264: 85-123. https://doi.org/10.3897/zookeys.264.4304 - Crabo, Lars; Davis, Melanie; Hammond, Paul; Mustelin, Tomas; Shepard, Jon (Zenodo, 2013)
Figures 38-44 - Male genitalia of Noctuidae. Ventral aspect of aedeagus is shown. Distal uncus of Fig. 41 is inset. 38 Resapamea diluvius Crabo, paratype, USA, WA, Grant Co., Potholes 39 Resapamea passer (Guenée), USA, WA, Douglas Co., 5 km ESE of Orondo 40 Resapamea angelika Crabo, holotype, USA, NV, Elko Co., Angel Lake 41Resapamea mammuthus Crabo, holotype, Canada, YT, Old Crow 42 Resapamea hedeni (Graeser), Russia, Magadan Oblast, Tenkinsky District, Stokovyi 43 Fishia nigrescens Hammond & Crabo, paratype, USA, OR, Klamath Co., 6 mi. SE of Klamath Falls 44 Xestia perquiritata orca Crabo & Hammond, paratype, USA, WA, Clallam Co., Neah Bay.